Update on the recent development of allosteric modulators for adenosine receptors and their therapeutic applications - Pasquini, Silvia; Contri, Chiara; Cappello, Martina; Borea, Pier Andrea; Varani, Katia; Vincenzi, Fabrizio (Frontiers in Pharmacology, 2022)
Adenosine receptors (ARs) have been identified as promising therapeutic targets for countless pathological conditions, spanning from inflammatory diseases to central nervous system disorders, from cancer to metabolic diseases, from cardiovascular pathologies to respiratory diseases, and beyond. This extraordinary therapeutic potential is mainly due to the plurality of pathophysiological actions of adenosine and the ubiquitous expression of its receptors. This is, however, a double-edged sword that makes the clinical development of effective ligands with tolerable side effects difficult. Evidence of this is the low number of AR agonists or antagonists that have reached the market. An alternative approach is to target allosteric sites via allosteric modulators, compounds endowed with several advantages over orthosteric ligands. In addition to the typical advantages of allosteric modulators, those acting on ARs could benefit from the fact that adenosine levels are elevated in pathological tissues, thus potentially having negligible effects on normal tissues where adenosine levels are maintained low. Several A1 and various A3AR allosteric modulators have been identified so far, and some of them have been validated in different preclinical settings, achieving promising results. Less fruitful, instead, has been the discovery of A2A and A2BAR allosteric modulators, although the results obtained up to now are encouraging. Collectively, data in the literature suggests that allosteric modulators of ARs could represent valuable pharmacological tools, potentially able to overcome the limitations of orthosteric ligands.